Design and configuration analysis of dual robotic arm via denavit hartenberg parameters approach - Abdalla Imadeldin, Abdelrahim Mohamed (2021)
Robotic arms are widely used in industry to complete tasks which is difficult to be performed by human being due to high repeatability or hazardous environment. However, due to the complexity and quality required by some applications where two arms are required, the human ability to perform those tasks sustains. This project presents a conceptual design and configuration analysis of 11 Degrees of Freedom (DOF) dual robotic arm using SOLIDWORKS and MATLAB. The analysis is via Devanit Hartenberg approach. The design is built to solve the current challenges faced by industry in term of workspace optimization and cost reduction with respect to the complexity of tasks performed by human labors in production assembly nowadays in industry due to the higher accuracy and better performance of human labor in term of speed which is required due to the nature of the tasks performed. The structural design is built using SOLIDWORKS and then the frame structure and configuration is performed using Robotics Toolbox (RTB) in MATLAB, followed by the analysis of the workspace and validation of efficiency. The analyzed results shown an improvement in term of performed tasks complexity and optimization in workspace required by 43.4% minimization in term of horizontal area, in addition to significant reduction in collision chances between arms. In general, the project provided a suitable replacement for two single robotic articulated arms in assembly line in industry.